Software development activity cycles : collaborative development, continuous testing and user acceptance - Rose, Robert F. (Apress, 2022)
The principal benefit this book is to provide a holistic and comprehensible view of the entire software development process, including ongoing evolution and support. It treats development as a collaborative effort with triad communication between a tester, a programmer, and a representative from the user community or a Subject Matter Expert (SME). Progress is measured by user acceptance in each cycle before proceeding to the next step of an activity. There is no test stage in the DPAC model: continuous testing is represented in the backswing (Check Phase) of each activity cycle. This approach posits that there exists some "happy path" that represents the intent of the project as declared by the objectives of a Vision Statement, and that this path can be revealed by an iterative and incremental process of "freeing the statue from the stone." As the image of this path unfolds, more waste is removed while retaining conceptual integrity. The example presented herein walks the reader through an application of the model. This book should be of great interest to Product and Project Managers new to the concept of a lean agile development effort, and all practitioners of an agile methodology or those considering or just beginning an agile journey. What You'll Learn See how the various disciplines constituting the software development process come together Understand where in the development process management, you can exercise measurement of progress and control Review how a quality engineering program will positively affect the quality of the development process Examine how the quality of the development process profoundly affects the quality of the software system Who This Book Is For Managers, from the C-Suite (CEO,CXO, CIO) to line managers including project managers, and practitioners including programmers, testers, and mid-level managers (Technical Project Managers, Software Quality Engineers, and Coaches). Also, Agile enthusiasts who are looking for a software development methodology on which to place their hat.